"They told me all mothers have worries", stillborn mother's experiences of having a 'gut instinct' that something is wrong in pregnancy: Findings from an international case–control study. (July 2018) - Warland, Jane; Heazell, Alexander E.P.; Stacey, Tomasina; Coomarasamy, Christin; Budd, Jayne; Mitchell, Edwin A.; O'Brien, Louise M.
Highlights: The risk of stillbirth is 22.5 fold higher in those who reported a "gut instinct" than in those that do not experience this feeling. The gut feeling is most likely to be reported as enduring from the beginning of the pregnancy or in response to perceived changes in fetal movement. Some women reported they had difficulty in expressing their concerns and "being heard". Abstract: Objective: To describe and explore 'gut instinct' that something was wrong in women who identified that they experienced gut instinct during pregnancy. Method: A case–control study utilising an international web-based questionnaire. Stillborn cases ( n  = 146) and liveborn controls ( n  = 234) answered the gut instinct question within 30 days of the pregnancy ending. Of those, 84 cases and 27 controls also provided qualitative comment data. Descriptive statistics were used for the question, with a fixed option and summative content analysis was used to analyse the comment data. Findings: In all, 110 (75%) of the stillborn cases answered "yes" to the gut instinct question vs only 28 (12%) of the controls who had a livebirth meaning the risk of stillbirth was 22.5 fold higher in those who experience "gut instinct" than in those who do not experience this feeling. Four themes were identified from the comment data namely: When the gut instinct occurred; How the gut instinct made the woman feel; Dreams and other related phenomena; Reassured by someone or something. Conclusions: Women who had a stillborn baby reported a "gut instinct" that something was wrong more frequently than mothers of a live born baby. Our findings may be influenced by recall negativity bias, and a prospective study is needed to confirm or refute our findings. The possibility that "maternal intuition" exists during pregnancy and responds to changes in fetal or placental health merits further exploration. Implications for practice: Maternity care providers should be alert to the woman when she expresses intuitive feelings, as well as asking her to report her concerns and act appropriately to assess and manage fetal wellbeing.